Mutational analysis of a cohort with clinical diagnosis of familial hypercholesterolemia: considerations for genetic diagnosis improvement - Medeiros, Ana Margarida (2015)
PURPOSE: Familial hypercholesterolemia (FH) is a common autosomal dominant disorder of lipid metabolism caused by mutations in LDLR, APOB, and PCSK9. To fulfill the World Health Organization recommendation, the Portuguese FH Study was established. Here, we report the results of the past 15 years and present practical considerations concerning the genetic diagnosis of FH based on our experience. METHODS: Our approach comprises a biochemical and molecular study and is divided into five phases, including the study of whole APOB and functional assays. RESULTS: A total of 2,122 individuals were enrolled. A putative pathogenic variant was identified in 660 heterozygous patients: LDLR (623), APOB (33), and PCSK9 (4); 8 patients presented with homozygous FH. A detection rate of 41.5% was observed. A stricter biochemical criteria was shown to improve patient identification. Overall, we have identified 3.4% and 80% of all heterozygous and homozygous patients, respectively, estimated to exist in our country. CONCLUSION: The Portuguese FH Study has established the genetic diagnosis of FH in Portugal and is committed to continue the investigation of the genetic complexity of FH. Genetic diagnosis of FH should be expanded to include the study of all coding/flanking regions of APOB and functional in vitro studies, to improve the correct patient identification, and to avoid misdiagnosis.